2023
DOI: 10.1007/s11069-023-05887-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and characterisation of extreme wind gust hazards in New South Wales, Australia

Abstract: Extreme wind gusts cause major socioeconomic damage, and the rarity and localised nature of those events make their analysis challenging by either modelling or empirical approaches. A 23-year long data record from 29 automatic weather stations located in New South Wales (eastern Australia) is used to study the distribution, frequency and average recurrence intervals (ARIs) of extreme gusts via a peaks-over-threshold approach. We distinguish between gust events generated by synoptic phenomena (e.g. cyclones and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous studies have performed goodness‐of‐fit tests and have demonstrated that the GPD and GEV models are suitable for modeling wind and rainfall extremes in the region of interest (Green et al., 2012; Holmes, 2002, 2019; Johnson & Green, 2018; Wang et al., 2013). The reader is also referred to (El Rafei, Sherwood, Evans, & Dowdy, 2023) in which we demonstrate using quantile plots and return level plots a good fit between the GPD model and the station data from the Sydney region.…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…Previous studies have performed goodness‐of‐fit tests and have demonstrated that the GPD and GEV models are suitable for modeling wind and rainfall extremes in the region of interest (Green et al., 2012; Holmes, 2002, 2019; Johnson & Green, 2018; Wang et al., 2013). The reader is also referred to (El Rafei, Sherwood, Evans, & Dowdy, 2023) in which we demonstrate using quantile plots and return level plots a good fit between the GPD model and the station data from the Sydney region.…”
Section: Methodsmentioning
confidence: 54%
“…Therefore, the threshold value is specific to each station and not pre‐fixed for the entire region. See (El Rafei, Sherwood, Evans, & Dowdy, 2023) for more details on the algorithm and event classification technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation